Active alpha : - Dorsey, Alan H. (John Wiley & Sons, 2007)
Active alpha is the quest for every sophisticated investor. This book covers all of the key alpha sources currently mined by active managers, reduces the complexity of the subject, and helps the investor get started in the right direction